Safety and Comfort of Hybrid Anti Roll Bar System for Improved Cornering Stability (International Journal of Engineering & Extended Technologies Research (IJEETR), 2026)
Stiffness and stability are of high importance for vehicles. Existing suspension systems reworking for vehicle stability increasing and they are not limited to own.One of the stability increases extra elements is the anti-roll bar.The anti-roll bar is a suspension system supporter in vehicles. However, bar stiffness  plays a critical role in vehicle stability. Bar stiffness can be managed on the predefined limitations.Therefore,a light,effective,and reliable vehicle system can be obtained.Aluminum metal matrix composites are widely used in various applications because of their higher mechanical and physical properties when compared with their base ALalloy.Metal matrix composites are fabricated by metal as a matrix material and metal,organic compound or ceramic as reinforcement. This experiment focuses on the changes in mechanical properties of LM6 reinforced with Boron carbide, Fly ash and Silicon carbide. Fabricate will be using stir-casting method. For this purpose, matrix of LM6 combined with various reinforcement weight percentages has been planned. (B4C-2.5%), (FA-2.5%) & (SiC-2.5%). The mechanical behavior such as Hardness, Tensile strength, Compressive strength will be evaluated.The optical properties will be evaluated through SEM analysis. Various stress analysis evaluated through Solid works with and without reinforcements.
Keywords: vehicle stability; AL alloys ceramic as reinforcement; Compressive strength; Metal matrix; SEM analysis.